Functional food and human health - Rani, Vibha; Yadav, Umesh Chand Singh; Ohio Library and Information Network (Singapore : Springer, 2018)
Global health and the increasing incidence of various diseases are a cause for concern, and doctors and scientists reason that the diet, food habits and lifestyle are contributing factors. Processed food has reduced the nutritional value of our diet, and although supplementing foods with various additives is considered an alternative, the long-term impact of this is not known. Many laboratories around the world are working to identify various nutritional components in our daily food and their effect on human health. These have been classified as Nutraceuticals or functional food, and they may have preventive and therapeutic effects in a number of pathologies associated with modern dietary habits and lifestyles
Keywords: Functional foods; Nutrition; Electronic books